Новые виды слизистых споровиков (Myxosporidia) рыб некоторых водоемов Западной Грузии - Чернова, Т.Н. (Вестник зоологии, 1970)
Four new species of mucous sporovics are described belonging to the Myxidiunt, Myxosoma and Myxobolus genera. Myxidium schulmani Chernova sp. n. was found in the kidneys of Rutilus rutilus (Linne) and Scardinius erythrophthalmus (Linne) from lakes Paleostomi and Japana. Myxosoma lomi Chernova sp. n. was found in the gills and kidneys of Rutilus rutilus (Linne) from lake Paleostomi. Myxobolus baueri Chernov a sp. n. was found in the gills, heart wall, urinary bladder wall, kidneys, gall-bladder wall, liver, spleen, swimming bladder wall, genital glands, intestine wall, vitreous body oi Tinea tinea (Linne) from lake Japana. Myxobolus crassus Chernova sp. n. was found in the gills and intestine wall of Tinea tinea (Linne) from lake Japana. Pictures of this species are given.